THE INTERACTION EFFECT OF TEACHING STRATEGIES AND GENDER ON STUDENTS’ ACHIEVEMENT IN GOVERNMENT - Friday Fidelis Anyima; Obiageli Ifeoma Ikwuka; Lilian-Rita Akudolu (Indonesian Journal of Educational Studies, 2025)
In this study quasi-experimental design was adopted, employing a pretest–posttest, non-equivalent control group approach. A sample of 200 students was selected from four secondary schools using stratified random sampling. The experimental group was taught using the interactive/constructivist strategy, while the control group received instruction through the traditional lecture method. Data were collected using the Government Achievement Test (GAT), which was validated and yielded a reliability coefficient of 0.82. The research was guided by two questions and two null hypotheses tested at a 0.05 level of significance using Analysis of Covariance (ANCOVA). Findings revealed that students taught with the interactive strategy achieved significantly higher mean scores in Government than those taught with the lecture method. However, gender was not a significant factor in determining students’ achievement, as both male and female students performed comparably under both strategies. Furthermore, the interaction between teaching strategy and gender was not significant, indicating that the effectiveness of instructional strategies transcends gender differences.